Influence of Baduanjin on cardiopulmonary function in long-term practitioners and beginners - Shi, Mengni; Wu, Zhiwei; Zhou, Xin; Fang, Min; Zhu, Qingguang (Frontiers in Sports and Active Living, 2024)
Objective Baduanjin, a traditional Chinese exercise for health enhancement and chronic disease prevention, has been practiced for millennia. However, studies on the exercise intensity of Baduanjin are limited. Most existing studies focus on its general health benefits rather than quantifying its specific intensity levels. This study aims to measure and compare the exercise intensity indices of long-term Baduanjin practitioners and beginners, providing insights into its mechanisms for disease prevention and treatment and supporting the scientific formulation of clinical exercise prescriptions. Methods Twenty healthy adults aged 35–45 years old and the mean BMI was 24.45 were recruited and divided into a beginner group (A group, no prior practice, 10 participants) and a skilled group (B group, practice duration ≥3 years, 10 participants). The Italian Cosmed/K5 wireless portable cardiopulmonary testing system was used to measure indicators during the practice. Results Within-group analysis revealed statistically significant differences in oxygen consumption (VO2), oxygen consumption per kilogram of body weight (VO2/kg), metabolic equivalent (METs), heart rate (HR), oxygen pulse (VO2/HR), respiratory rate (RR), and minute ventilation (VE) between exercise and resting states in both the B and A groups (P < 0.001). In between-group comparisons, resting HR was significantly lower in the B group compared to the A group (P < 0.01). During Baduanjin practice, significant between-group differences were found in METs, HR (P < 0.01), and RR (P < 0.05), with the A group exhibiting higher values for METs, HR, and RR than the B group. Conclusion Baduanjin positively impacts cardiovascular function and exercise performance, with long-term practitioners showing significantly better cardiovascular recovery and overall function.